Validation of Horizontal Genes Transfer Using Selected Clinical Strain of P. Mirabsilis for Swarming Activity - Rusul Idan Mohsin Ali1,3, Muslim Idan Mohsin2 , Abbas Al-Muhna3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Proteus mirabilis expresses several virulence factor which enable them to colonize, surviveand grow in the host organism. This study was to investigate whether P. mirabilis could deliver a spontaneousplasmids to competent strains, and to investigate whether P. mirabilis can be as a donor strains to deliverytheir virulent such as adhesion and swarming activity.Methodology: PCR was used to detect the motility genes that encoded in P. mirabilis. Using alsotransformation assay to transfer these genes of Proteus to standard strain. PCR technique used again todetermine the whether genes were transfer or not after transformation.The results: the findings show that 9 (filD, flhC, flhD, motA, motB, fliL, flaA, flgM,) genes were encodedon chromosomal DNA of P. mirabilis. Interestingly data, only 3 (flaA, flgM and filD ) genes were carriedon different plasmids of P. mirabilis. The results also show that spontaneous plasmids of P. mirabilis cantransfer to standard strains of E. coli. We found one gene transfer to E. coli S17? filD. The gene(filD) has arole in the P. mirabilis swarming motility.Conclusions: we demonstrated that these genes can carry not only on chromosomal DNA but also inPlasmidal DNA and transferring genes associated-characteristics, swarming motility